PERANAN UNGKAPAN TRADISIONAL DALAM MEMBANGUN TATANAN SOSIAL DAN SISTEM KOMUNIKASI MASYARAKAT MELAYU JAMBI - Rustam Rustam (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2016)
Traditional phrases as part of Jambi Malay cultural tradition or culture are seloko, proverb, petitih-petitih, pantun, iwa, hum, and so on. These traditional forms of expression have meanings, ideas, messages and objectives that need attention, both in the disclosure of the language and the social context of the speaker's community. A man is said to be cultured or cultured if the person is able to implement the traditional expression of his thoughts, feelings and actions through the context of the social order and the system of his cultivation. To answer the problem, it needs to be described the role of traditional expression in building social order and communication system of Jambi Malay society. As a basis for thinking in medeskripsikan role of traditional expression used concept and theory of traditional expression, sociololinguistic, and pragmatik. The phenomenon of the traditional expression is analyzed by using the socio-pragmatic approach and the extra lingual pad method. Based on the results of traditional expression analysis, it was found that the traditional expression was able to build a high social order and high-level in Jambi Malay society, that is adat philosophy, customary purpose, customary law basis, adat institution position, custom institution function, implemented concretely in the social cultural order of the wearer. It is characterized by the existence of customary civil law, namely private law, kinship law, marriage law, inheritance law, and customary law. The disclosure of the noble social-cultural order was also poured through the text of oral discourse depicted in the communication system of Jambi Malay community by using custom kato. Disclosure of Jambi Malay community communication system using pragmatic principles with maxim of quality, maxim of quantity, maxim of relationship, way maxim, maxim of wisdom, maxim of generosity, maxim of praise, maxim of humility, maxim of agreement, and maxim of sympathy.